2005
DOI: 10.1634/stemcells.2004-0256
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent Stem Cells in Human Corneal Stroma

Abstract: Keratocytes of the corneal stroma secrete a specialized extracellular matrix essential for vision. These quiescent cells exhibit limited capacity for self-renewal and after cell division become fibroblastic, secreting nontransparent tissue. This study sought to identify progenitor cells for human keratocytes. Near the corneal limbus, stromal cells expressed ABCG2, a protein present in many adult stem cells. The ABCG2-expressing cell population was isolated as a side population (SP) by cell sorting after exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
305
1
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(332 citation statements)
references
References 44 publications
19
305
1
7
Order By: Relevance
“…In the same year, isolation of stromal stem cells from human cornea was also reported (139). In this latter study, some stromal cells have shown ABCG2 positivity (see also Fig.…”
Section: Stromal Stem Cellsmentioning
confidence: 60%
See 1 more Smart Citation
“…In the same year, isolation of stromal stem cells from human cornea was also reported (139). In this latter study, some stromal cells have shown ABCG2 positivity (see also Fig.…”
Section: Stromal Stem Cellsmentioning
confidence: 60%
“…Based on this observation, the side population was selected from the cells released from the corneal stroma by digestion with collagenase and hyaluronidase. In culture, these side population cells showed clonal growth and could be differentiated to express keratocyte, chondrogenic and neurogenic markers (139). The same group has concomitantly showed that while these undifferentiated corneal stromal stem cells predominantly express generic stem cell related genes (Bmi-1, Kit, Notch-1, Six2, Pax6, ABCG2, Spag10, p62/OSIL) in adherent cultures, when passaged in suspension in serum free medium with FGF2 and insulin, they form spheroid pellets, in which keratocyte-like cells secrete an ordered ECM and express mRNAs of known (keratocan, PTGDS, ALDH3A1) and potential (FLJ30046/SLAIN, CxAdR, PDK4, MTAC2D1, F13A1) keratocyte markers (140).…”
Section: Stromal Stem Cellsmentioning
confidence: 99%
“…Other researchers similarly described high cellularity in the anterior limbal stroma in phalloidin green and propidium iodide stained confocal sections. 19 The cellular components in this region include (i) ABCG2 and PAX6 positive multipotent stromal stem cells, 20 (ii) vimentin positive mesenchymal cells, expressing ESC markers 9 , and (iii) CD34, CD31, Flk-1,VWF positive stromal cells. 12 In another study, we demonstrated the presence of clusters of CD90 and CD105 positive MSCs in the native anterior limbal stroma, along with vimentin positive mature keratocytes distributed singly (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Since its initial application in bone marrow HSCs, the side population technique based on Hoechst 33342 efflux has been adapted to identify putative stem cells and progenitors in many normal tissues (Zhou et al, 2001;Asakura & Rudnucki, 2002;Leckner et al, 2002;Alvi et al, www.intechopen.com 2003; Summer et al, 2003;Budak et al, 2005;Du et al, 2005, Hussain, et al, 2005. SP cells have also been found in a number of established cancer cell lines as well as tumor samples and have been shown to have stem cell-like properties, overexpress ABCG2, and possess inherent drugresistance (Kondo et al, 2004;Hirschmann-Jax et al, 2004;Haraguchi et al, 2005;Seigel et al, 2005, Chiba et al, 2006.…”
Section: Detection and Identification Of Cscsmentioning
confidence: 99%